Pengaruh Pertunjukan Orgen Tunggal Terhadap Eksistensi Rabab Pasisia di Kecamatan Lengayang Kabupaten Pesisir Selatan - Silpa Parwati; Harisnal Hadi (SENDRATASIK UNP, 2020)
This study aims to find and describe the effect of Orgen Tunggal performance on the existence of Rabab Pasisiain Kambang Village, Lengayang District, South Pesisir Regency. This is a qualitative research using a descriptivemethod. The main instrument in this study was the researcher it self and was assisted by supporting instruments such as writing instruments and cameras. The data were collected through literature study, observation, interview, and documentation. The steps for analyzing the data are collecting the data, describing the data, and making conclusions. The results show that Orgen Tunggal performance can affect the existence of Rabab Pasisia in Kambang Village community, Lengayang District, South Pesisir Regency. Nowadays, people no longer understand the messages contained in Rabab, and Rababis viewed as entertainment only. There are factors which influence the existence of RababPasisia. Internally, the community more likely enjoys Orgen Tunggal. The people no longer understand the education value in Rabab, so it makes Rabab Pasisia unattractive. Externally, modernization and globalization rises. The existence of Orgen Tunggal which is increasingly popular in the community of KambangVillage, Lengayang District, affects the existence of Rabab as traditional entertainment which has moral messages.Gradually it also affects the intensity of Rabab performance on the community who enjoys Rabab, on messages Rabab delivers, on the existence of Rabab, and on the performance of Rabab. Rabab undergoes a few updates so that it still exists and is favored by the community. One of which is a form of Raun Sabalik which has pleasant rhythms.